Association between immune system parameter and clinical characteristics among patients with solid cancer - Cahyanur, Rahmat; Widhani, Alvina; Pantoro, Nico Iswanto; Madadika, Annisa Tsana (Faculty of Medicine Universitas Indonesia, 2024)
BACKGROUND Lymphopenia has been reported to be a major predictor of chemotherapy-related toxicity. This study aimed to investigate the correlation between neutrophils, lymphocytes, CD4, and CD8 in solid cancer patients and cancer clinical characteristics. METHODS This was a cross-sectional study of patients who will undergo chemotherapy at the Hematology and Medical Oncology Clinic, Cipto Mangunkusumo Hospital, from June to September 2023. Clinical characteristics, CD4 and CD8 levels, and neutrophil and lymphocyte counts were assessed at the first visit. A comparative test was carried out on the patients’ average CD4, CD8, neutrophil, and lymphocyte counts. RESULTS Types of cancer were associated with CD4 levels. Patients with head and neck cancer had lower CD4 levels (411.3 [119.3–1,427.5] cells/mm³) compared with colorectal (514.7 [129.2–861.3] cells/mm³), breast and gynecological (567.5 [180.1–939 cells/mm³), and other cancers (681.4 [175.1–2,056.9] cells/mm³), with p = 0.009. Patients aged ≥40 years had higher CD8 levels than those aged <40 years (376.4 [142.8–1,293.1] cells/mm³ versus 565.3 [185.9–1,944] cells/mm³, p = 0.01). Additionally, lymphocyte count was associated with cancer type, with the lowest number in head and neck cancer (1,380 [280–2,660] μl, p = 0.044). CONCLUSIONS CD4 levels and lymphocyte counts were associated with the cancer type, whereas CD8 levels were influenced by age.